Race and the Revolutionary Impulse in The Spook Who Sat by the Door - Greenlee, Sam, 1930-2014; Yaquinto, Marilyn; Wall, David C.; Martin, Michael T. (Book collections on Project MUSE., 2018)
Ivan Dixon's 1973 film The Spook Who Sat by the Door captures the intensity of social and political upheaval during a volatile period in American history. Based on Sam Greenlee's novel by the same name, the film is a searing portrayal of an American black underclass brought to the brink of revolution. This series of critical essays situates the film in its social, political, and cinematic contexts and presents a wealth of related materials, including an extensive interview with Sam Greenlee, the original United Artists' press kit, numerous stills from the film, and a transcription of the screenplay. This fascinating examination of a revolutionary work foregrounds issues of race, class, and social inequality that continue to incite protests and drive political debate.